Disruptive trends in computer aided diagnosis - Das, Rik, 1978-; Nandy, Sudarshan; Bhattacharyya, Siddhartha, 1975- (Boca Raton : Chapman & Hall/CRC Press, 2021)
"This book is an attempt to collate novel techniques and methodologies in the domain of content- based image classification and deep learning/machine learning techniques to design efficient computer aided diagnosis architecture. It is aimed to highlight new challenges and probable solutions"--
OCLC-licensed vendor bibliographic record.
Keywords: Diagnosis -- Decision making -- Data processing; Clinical medicine -- Decision making -- Data processing; COMPUTERS / Machine Theory; COMPUTERS / Computer Graphics / Image Processing (see also PHOTOGRAPHY / Techniques / Digital); COMPUTERS / Computer Science